Cultivo in vitro de Peltophorum dubium (Sprengel) Taubert: multiplicação, senescência foliar e calogênese - Candido, Danieli Ferneda (2013)
Peltophorum dubium (Sprengel) Taubert is a native forest species with many possible uses, with great potential for commercial plantations. However, there is little information on the production of seedlings of this species, which, together with the inherent limitations of tree species, impedes the setting of breeding programs and, therefore, the establishment of stands of appropriate genetic quality. Studies related to the Peltophorum dubium propagation by tissue culture techniques can help in this regard. Therefore, this study aimed to evaluate methodologies for in vitro culture of Peltophorum dubium, with the specific purpose of increasing rates of multiplication of the species and reduce leaf senescence. Furthermore, we tried to establish an efficient methodology for the indirect organogenesis, which can be an alternative way to induce organs. On in vitro multiplication and leaf senescence were investigated different sources and concentrations of cytokinins 6-benzylaminopurine (BAP), kinetin (KIN), isopentenyladenine (2iP), and thidiazuron (TDZ), combined one with each other, or isolated, and its association with α-naphthaleneacetic acid (NAA) and in the case of kinetin, 2iP and TDZ, also with BAP. In indirect organogenesis, we evaluated the effect of different concentrations of 2.4-D and various explants cultured in the presence or absence of light. It can be concluded that the use of cytokinin 2iP, in the evaluated concentrations in the presence of NAA or in association with NAA and BAP, has no effect on in vitro multiplication of the epicotyls containing cotyledonary node of Peltophorum dubium. Further, after 21 days of in vitro culture, under conditions of high temperature, occurs expressive leaf senescence. Cytokinins BAP, KIN, 2iP and TDZ, in evaluated concentrations, do not influence the in vitro multiplication of Peltophorum dubium. To maintain controlled leaf senescence when TDZ is used is dispensable using NAA, however, when the cytokinin 2iP is employed, the presence of NAA contributes to a reduction in the number of senescent leaves. Generally, from 21 days of in vitro culture the auxin and cytokinins used (NAA, 2iP and TDZ) start to have a significant effect on the occurrence of leaf senescence, which will depend on the combination of growth regulators. Can be also checked that the presence of TDZ, 2iP and NAA at the concentrations tested have no influence on survival, establishment and number of leaves formed in Peltophorum dubium during the initial in vitro culture of epicotyls containing cotyledonary node, have been observed high averages for these variables. Furthermore, the combination of NAA and TDZ has significant deleterious effect on in vitro survival of Peltophorum dubium explants during the first 30 days of subculture. This association also has significant deleterious effect on in vitro establishment and number of new shoots in shoot apical segments during first 30 days of subculture of Peltophorum dubium. The presence of 2iP and NAA at the concentrations tested doesn't have influence on survival, establishment, number of shoots and number of leaves formed in Peltophorum dubium during the first subculture of 30 days. The callogenesis is maximized in the presence of 20 μM of 2.4-D in cotyledon and hypocotyl segments. In the absence of 2.4-D hypocotyl are more efficient in callus formation. There is a high phenolic oxidation, but that, in general, does not impair the formation of callus, mainly in hypocotyls and cotyledon segments. There are 100% of root formation in cotyledon segments in the presence of light and nutritive medium supplemented with 40 μM of 2.4-D; in the absence of light and in the presence of 20 μM auxin rooting is also satisfactory.